DECENTRALIZATION AND TOURISM DEVELOPMENT: COMPARING PUBLIC ADMIISTRATION STRATEGIES FOR TOURISM IN PADANG CITY AND BUKITTINGGI CITY - Diga Putri Oktaviane; Harapan Tua (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research examines how decentralization policy in Indonesia shapes public administration strategies in tourism destination development across two major cities in West Sumatera: Padang City and Bukittinggi City, which possess distinct geographical characteristics, governmental structures, and fiscal capacities. Through a comparative literature study finds that Padang City adopts a coastal modernization strategy oriented toward infrastructure and MICE (Meetings, Incentives, Conventions, and Exhibitions), whereas Bukittinggi City develops a heritage conservation and community based governance approach. Decentralizations demonstrates a characteristics of asymmetrical governance, where fiscal capacity and geographical context significantly determine the local government’s ability to formulate tourism strategies. This study contributes to the theory of destination governance and decentralizations by ooffering the perspective that regional autonomy does not automatically enhance policy effectiveness: rather, it must be supported by institutional capacity, collaboration, and policy fit with the unique characteristics of the tourist destination.